The Effectiveness of Emotionally Focused Couple Therapy in Improving Marital Adjustment and Couples’ Intimacy - M. Davoudvandi; Sh. Navabinejad, Ph.D.; V. Farzad, Ph.D. (خانواده و پژوهش, 2018)
The present study[4] sought to investigate the effectiveness of emotionally focused couple therapy in improving marital adjustment and couples’ intimacy. This quasi-experimental research had a pretest posttest control group design with a follow-up assessment. Thirty-two parents of school-aged children (16 couples) who were the clients of counseling clinics of Education Departments in Tehran were selected through convenience sampling method. These individuals were randomly assigned to two groups of emotionally focused couple therapy (N=16, 8 couples) and control (N=16, 8 couples). The emotionally focused couple therapy group was subjected to 10 treatment sessions and the control group was assigned to a waiting list. There was a subsequent follow-up two months later. The instruments comprised Spanier’s Dyadic Adjustment Scale (1976) and Walker and Thompson’s Intimacy Scale (1983). The data were analyzed using two-factor repeated measures ANOVA. Results showed that emotionally focused therapy led to effective and lasting changes in couples’ adjustment and intimacy components (p<0.05). Accordingly, the emotionally focused couple therapy can be used as an effective strategy to improve marital relationship, adjustment, as well as intimacy, and it ultimately leads to long-lasting, stable marriages.